Togo : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
Togo’s risk of external debt distress continues to be moderate with heightened overall risk of debt distress—unchanged from the previous Debt Sustainability Analysis (DSA) published in April 2017. Alternative scenarios and stress tests suggest, however, that external public debt could accumulate rapidly, pushing Togo above the external debt-distress threshold for the present value (PV) of public and publicly guaranteed (PPG) debt-to-GDP. Togo’s domestic public debt burden remains high and reflects among others, persistently high deficits, materialized contingent liabilities and arrears accumulation. Baseline projections show that Togo’s PV of total PPG debt (external plus domestic) -to-GDP ratio will reach the 38 percent benchmark by 2025, down from 73.1 percent in 2017 -with the bulk constituting domestic debt obligations. This analysis highlights the need for sustained fiscal consolidation, improved debt management, and macroeconomic policies to reduce the level of public debt to prudent levels over the medium term.